PARENT INVOLVEMENT IN EDUCATION: BARRIERS AND THEORETICALMODELS FOR EFFECTIVE PARTNERSHIP - Winkler, Ram (E-Journal VFU, 2025)
The parents’ involvement in education is defined as the constellation of actions  performed at home and at school in order to advance their children’s success in academic,  social, and behavioral aspects. The research literature differentiates between types of  involvement such as involvement at home as opposed to involvement in the school, when every  type has unique influence on the students’ success. This involvement contributes greatly to  academic and emotional achievements, but deals with diverse challenges, including gaps in perceptions, socioeconomic barriers, levels of education, family structure, and number of  children in the family. A number of theoretical models provide a framework for the  understanding of the factors and means that shape the parental involvement. Despite the  significant advantages of this involvement, there are systemic and personal barriers that make it difficult to realize the potential of involvement between the parents and the education system.
Keywords: barriers of involvement; theoretical models; parent-teacher communication; Parents’ involvement in education